Improvement of ecologically safe sediment processing technology - Aliev Makhmud; Nurmanov Sarvar; Tursunov Zarif; Khikmatova Nokhila; Radjabov Shahzod (E3S Web of Conferences)
The processing of sludge formed in wastewater treatment plants is one of the most urgent tasks in ensuring the ecological safety of cities and has been promoted in recent years as one of the most complex, expensive and poorly studied problems in the field of water treatment. The purpose of the scientific article is to improve and study existing and new technologically feasible, highly efficient, environmentally safe sludge processing methods and technologies. Reinforcement of the process of gravitational density of wastewater sediments was studied. Scientific research was carried out at the first stage with excess activated sil, which is formed during the biochemical treatment process at the station. Ammophos and superphosphate were used as reagents. In order to determine technological and economic feasibility of using iron-containing coagulants in enhancing the process of active silt densification, studies were carried out to study its densification kinetics. As a result of research, superphosphate was found to be the most effective in the density of overactive silt with local reagents.